The Relationship between Iron Deficiency Anemia and the Incidence of Febrile Convulsions - Khan, Mohsin; Khan, Niama; Jalil, Mudassir Abdul; Ali, Muhammad Asfandiyar; Khan, Jawad Khan; Khan, Mohsin (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To determine the role of iron deficiency anemia in patients with febrile convulsions in the 06 to 60 months in a tertiary care hospital. METHODOLOGY This cross-sectional study was undertaken at Ayub Teaching Hospital, Abbottabad, from January 2020 to February 2022. Patients with typical and atypical febrile seizures were recruited for the study, while patients with neurodegenerative diseases, meningoencephalitis, epilepsy, trauma, nephritic syndrome, and hypertensive seizures were excluded from the study. Iron deficiency was identified concerning a complete blood count. The data were analyzed in SPSS version 21, and the significance value was kept at < 0.005. RESULTS In the present study, 102 patients were enrolled. The mean age of the sample was 15 months, with an age range of 6-54 months. The male-to-female ratio was 2:1. The mean haemoglobin (HB) of the sample observed was 9.9±1.9, mean corpuscular volume (MCV) 73±13, red cell distribution width (RDW) 16±7.9 white cell count (WBC) 12.9±7.1 and platelets of 312±180. The use of cow milk in febrile seizures was 41%, and only 33% of parents were unaware of proper milk dilution. CONCLUSION We concluded that patients with atypical febrile seizures and those with seizures more than once have a significantly higher degree of iron deficiency anemia than those with typical febrile seizures. Moreover, the group with prolonged seizures has severe anemia compared to the group with brief seizures.